The governors of New Jersey : biographical essays - Birkner, Michael J., 1950-; Linky, Donald, 1946-; Mickulas, Peter, 1968- (Rivergate regionals., 2014)
This revised edition is a thorough reference work on the New Jersey governorship, one of the strongest in the nation. It is brought current with the addition of essays on Governors Brendan T. Byrne, James Florio, Christine Todd Whitman, Donald DiFrancesco, James McGreevey, Richard Codey, and Jon Corzine. Essays included in the original edition are amended, edited, and corrected as necessary by the original authors in light of new and relevant scholarship